2022
DOI: 10.7759/cureus.24182
|View full text |Cite
|
Sign up to set email alerts
|

Tibia Tuberosity Fracture and Patellar Tendon Rupture Combination in a Pediatric Patient: Case Report and Narrative Review

Abstract: A combination of tibial tuberosity (TT) fracture (TTF) along with patellar tendon (PT) rupture (PTR) is rare. We report a 15-year-old male who presented to our ED with acute knee pain and an inability to actively extend the knee after jumping during a basketball game. Diagnosis of simultaneous PTR is crucial as it changes clinical management. It is, therefore, important to maintain a high index of suspicion for the combination of TTF and PT injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The tibial tuberosity fragment can be secured with screws, Kirschner wires, staples, or trans-osseous sutures, while staples, trans-osseous suture, standard Krakow sutures, figure-ofeight tension band wiring, cerclage wire and suture bone anchor, potentially augmented with protective wire loop or semitendinosus graft have been described for patellar tendon reinsertion. 1,3,[7][8][9][10][11] Reinforcement of ligament repair can be done either with cerclage wire or fiber wire through a patella bone tunnel, as in our case. 3 Moreover, contralateral patellar tendon, quadriceps graft, hamstring graft, Achilles tendon allograft, or synthetic ligament augmentation has been described.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The tibial tuberosity fragment can be secured with screws, Kirschner wires, staples, or trans-osseous sutures, while staples, trans-osseous suture, standard Krakow sutures, figure-ofeight tension band wiring, cerclage wire and suture bone anchor, potentially augmented with protective wire loop or semitendinosus graft have been described for patellar tendon reinsertion. 1,3,[7][8][9][10][11] Reinforcement of ligament repair can be done either with cerclage wire or fiber wire through a patella bone tunnel, as in our case. 3 Moreover, contralateral patellar tendon, quadriceps graft, hamstring graft, Achilles tendon allograft, or synthetic ligament augmentation has been described.…”
Section: Discussionmentioning
confidence: 98%
“…Mousafeiris et al reported a fixation with two half-threated 6.5 mm cannulated screws for the tibial tubercle in a 15-years-old male and a bone anchor with two high resistance sutures placed according to Krakow technique. 10 Additional suture was placed through the quadriceps tendon in a figure-of-eight manner to enforce the repair. 10 Pereira et al performed a patellar tendon repair in a 15-years-old boy with two anchors augmented with a semitendinosus tendon autograft, and a fixation of the tubercle through two 4.5 mm cannulated screws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation